Visual Design of Pop-Up Book Publication Binturong the Rare Cat Bear - Syahputra, Dermawan; Tanjung, Muhammad Rusdi (CV. Publikasi Indonesia, 2024)
This thesis aims to design an engaging and educational pop-up book about the Binturong (Arctictis binturong), a nocturnal creature related to civets but distinguished by size. Known by various names in different regions, such as Binturong, Binturung, Menturung, or Menturun, this animal is referred to as Binturong, Malay Civet Cat, Asian Bearcat, Palawan Bearcat, or simply Bearcat in English. The wild population of Binturong has experienced a significant decline, leading to an elevation of its conservation status to Vulnerable (VU), according to the International Union for Conservation of Nature (IUCN). Binturong is listed among the protected species by the Indonesian government. The population decline is attributed to human intervention through exploitation, excessive hunting, deforestation, and forest fires. The responsibility of preserving the environment and biodiversity should concern society. Particularly, educating children, as the next generation, about the Binturong is crucial for understanding the importance of ensuring the sustainability of this species. Therefore, the pop-up book is considered an attractive educational medium. A pop-up book is an interactive form of literature with images that can be erected, aesthetically pleasing, and capable of movement. Thus, the pop-up book serves as an effective tool to enhance reading interest and knowledge about the Binturong.